Extending Student (R)esponse to (E)ngagement in a Bilingual Classroom: An Analysis of Identity-Infused Classroom Discourse - Ferraro, Marisa (Empowering Students Through Multilingual and Content Discourse, 2023)
The growing diversity of students in schools has raised important questions regarding how students learning English and discipline-content simultaneously succeed academically. This challenge has been exacerbated by disparities in resources among multilingual communities throughout the COVID-19 pande...
Keywords: dept.cur

Cultivating Language and Identity through Multimodal Literacies: Back to the StoryBoard - Ferraro, Marisa; Mendoza, Kristin Bengtson (Multimodal Literacies in Young Emergent Bilinguals: Beyond Print-Centric Practices, 2022)
Keywords: dept.cur